Проблемы осуществления транспортировки грузов в Арктической зоне РФ морским путем - Antipov, Evgeny Olegovich; Tutygin, Andrey Gennadyevich; Korobov, Vladimir Borisovich (Administrative Consulting, 2025)
The addressed problems arise in cargo shipping by marine vessels in the Arctic zone of the Russian Federation. The document identified 6 major challenges hindering these operations. There has been proposed a route optimization model in the northern delivery with the efficiency demonstrated in particular example.